Análise ultraestrutural e avaliação do sêmen de peixes neotropicais, Brycon orbignyanus, Rhamdia quelen e Brycon hilarii (Pisces, Teleostei) - Prieto Mojica, Camilo Alberto [UNESP] (2004)
Semen and testes samples were collected of male adults of Piracanjuba (Brycon orbignyanus). Jundiá (Rhamdia quelen) and Piraputanga (Brycon hilarii) in the Aquaculture Center of UNESP (CAUNESP) - Jaboticabal - SP (Brazil) and in the National Center of Research in Tropical Fish (CEPTA) - Pirassununga - SP (Brazil). Macroscopic analyses evidenced characteristics related to the color, aspect and volume. It was microscopically appraised: The motility, viability and cell concentration of the sperm. The main biochemistry components of the seminal plasm, ionic (sodium, potassium, magnesium and calcium), osmolality and glucose concentration were analyzed. For the accomplishment of the ultrastructural studies, fragments of testicular tissue were fixed in glutaraldehyde 2,5% and processed according to transmission electron microscope routine. The aim of this study was analyze comparatively, the seminal parameters and the structure of the spermatozoon of 3 neotropical fish species (Piracanjuba, Brycon orbignyanus, Piraputanga, Brycon hilarii and Jundiá, Rhamdia quelen). In the piracanjuba, the semen is yellowish and with aqueous aspect. In jundiá the color of the semen is white and with creamy aspect. In the piraputanga the coloration of the semen is whitish and milky aspect. Comparing these characteristics with the sperm concentration found in piracanjuba (2,72 x 109 ± 1,92 x 109 sp/mL), jundiá (4,57 x 1010 ± 1,50 x 1010 sp/mL) and piraputanga (6,46 x 109 ± 2,72 x 109 sp/mL) and with the values of the spermatocrit (5,5%, 93,5% and 16,6% respectively), we can observed that the more creamy semen, the bigger the sperm concentration. The piracanjuba presented the smallest value of percentage of sperm motility (77±6,74%). On the other hand, it was observed that the ionic composition varies among the species and inside of the same ones, due to factors as the environment or to the reproduction ...